Novel polylactic acid obtained by chemical and biochemical hydrolysis of kenaf fibre - Anuar, Hazleen (The Academy of Sciences for Developing World (TWAS), 2011)
In this project, the aim is to produce polylactic acid from kenaf fibre biomass through fermentation. Kenaf fibre is found to be naturally resistant to breakdown due to its structural sugars since it is a lignocellulosic material. Hence, it is difficult for microorganisms to use it directly as fermentation carbon source. Kenaf was underwent several pre-treatment methods such as hydrolysis to liberate sugars by either chemical hydrolysis (acid and base) or enzymatic hydrolysis. The best pre-treatment method that produced the highest glucose from biomass was then used in optimization for glucose conversion. This glucose was then fermented by Rhizopus oryzae to produce lactic acid. Then, the lactic acid was finally synthesized to polylactic acid through polycondensation process.